2009
DOI: 10.1007/s10498-008-9055-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry of Salt Lakes of the Qinghai-Tibet Plateau, China

Abstract: The authors have carried out scientific investigations of salt lakes on the Qinghai-Tibet Plateau since 1956 and collected 550 hydrochemical data from various types of salt lakes. On that basis, combined with the tectonic characteristics of the plateau, the hydrochemical characteristics of the salt lakes of the plateau are discussed. The salinity of the lakes of the plateau is closely related to the natural environment of lake evolution, especially the climatic conditions. According to the available data and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 3 publications
5
72
0
Order By: Relevance
“…From 12.0 to 7.5 cal ka BP, the humidity of the lake area was remarkably improved, as evidenced by the increased pollen concentrations, TOC and TN contents and decreased ostracod δ 18 O. Specifically, two peaks (11.0 and 8.5 cal ka BP) are notable for the pollen concentrations, TOC and TN contents, while the ostracod δ 18 O was generally low from 11.5-7.5 cal ka BP. Multiproxy results based on data synthesized after considering the proxies' different responses to the humidity and temper-ature of the lake area show that the best thermal-humid combination of Lake Qinghai should be at around 8.5 cal ka BP, reflecting the maximal intensification of the East Asian monsoon.…”
Section: 4 a Time Scalesmentioning
confidence: 97%
See 2 more Smart Citations
“…From 12.0 to 7.5 cal ka BP, the humidity of the lake area was remarkably improved, as evidenced by the increased pollen concentrations, TOC and TN contents and decreased ostracod δ 18 O. Specifically, two peaks (11.0 and 8.5 cal ka BP) are notable for the pollen concentrations, TOC and TN contents, while the ostracod δ 18 O was generally low from 11.5-7.5 cal ka BP. Multiproxy results based on data synthesized after considering the proxies' different responses to the humidity and temper-ature of the lake area show that the best thermal-humid combination of Lake Qinghai should be at around 8.5 cal ka BP, reflecting the maximal intensification of the East Asian monsoon.…”
Section: 4 a Time Scalesmentioning
confidence: 97%
“…However, climate for the northern Tibetan Plateau appears to have led to dry conditions, as evidenced by the semiclosed hydrological conditions, lowered water stands and increased water salinities for some lakes in this region, with no discharges of glacial-melting waters. For instance, the diatom assemblages of Lake Sipanguer are characterized by relative increases of benthic and epilithic diatoms, while those of and Zhacang Chaka are characterized by deposited mirabilite and gypsum [18]. For the late Holocene, the climate became drier, as indicated by intense shrinking of Tibetan lakes, as well as vegetation degradation (decreased pollen concentrations and increased relative percentages of dry species/genera) of the lake watersheds.…”
Section: Alpine Lakes In the Frigid Tibetan Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…GW41 that are higher than the allowable limit for drinking purposes. The previous studies have also revealed that As and Sr concentrations in water resources around boron deposit areas are generally higher (Helvaci and Alonso 2000;Helvaci et al 2004;Gemici et al 2008;Zheng and Liu 2009).…”
Section: Groundwatermentioning
confidence: 93%
“…drothermal origin for the boron present in lake deposits (Zheng et al, 1983;Wu et al, 1984;Zhang et al, 1999) based on the dense distribution of geothermal activities and springs in the lakes along activated graben systems (Zheng et al, 1989;Lü et al, 2013). Others interpretations have considered that the high boron concentration of geothermal water could contribute significantly to boron deposits in the nearby internally drained lakes, as suggested by the constant supply of boron from this source into the lakes and the consequent evaporation (Zheng et al, 1983;Wu et al, 1984;Zhang et al, 1999).…”
mentioning
confidence: 99%